2010
DOI: 10.1152/ajpregu.00525.2009
|View full text |Cite
|
Sign up to set email alerts
|

Endurance training enhances BDNF release from the human brain

Abstract: The circulating level of brain-derived neurotrophic factor (BDNF) is reduced in patients with major depression and type-2 diabetes. Because acute exercise increases BDNF production in the hippocampus and cerebral cortex, we hypothesized that endurance training would enhance the release of BDNF from the human brain as detected from arterial and internal jugular venous blood samples. In a randomized controlled study, 12 healthy sedentary males carried out 3 mo of endurance training (n = 7) or served as controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
256
5
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 375 publications
(284 citation statements)
references
References 45 publications
6
256
5
13
Order By: Relevance
“…133 Whether such improvements are coupled with increased CBF and vascular reactivity are unknown. A higher CBF and vascular reactivity outcome seems tenable given the established links between habitual physical activity, improved cognition, and increased availability of neurotrophins and growth factors in the brain that facilitate neurogenesis, synaptic plasticity, and angiogenesis, 134,135 which as outlined above, may underpin the improved brain vascular function. 136 Further, recent findings in both young 137 and older 138 adults indicate that vascular reactivity may mediate the positive exercise-cognition relation.…”
Section: Optimizing Cerebrovascular Adaptation Through Brain-targetedmentioning
confidence: 99%
“…133 Whether such improvements are coupled with increased CBF and vascular reactivity are unknown. A higher CBF and vascular reactivity outcome seems tenable given the established links between habitual physical activity, improved cognition, and increased availability of neurotrophins and growth factors in the brain that facilitate neurogenesis, synaptic plasticity, and angiogenesis, 134,135 which as outlined above, may underpin the improved brain vascular function. 136 Further, recent findings in both young 137 and older 138 adults indicate that vascular reactivity may mediate the positive exercise-cognition relation.…”
Section: Optimizing Cerebrovascular Adaptation Through Brain-targetedmentioning
confidence: 99%
“…In addition, the reduced stroke risk and improved long-term outcome as a result of physical activity have been postulated to be due to upregulation of endothelial NO synthase (Endres et al 2003;Gertz et al 2006). Additional mechanisms potentially contributing to this increased cerebrovascular reactivity include brain-derived neurotrophic factor (Seifert et al 2010) and insulin-like growth factor-1 (Llorens-Martin et al 2010). Furthermore, hypocapnic cerebrovascular reactivity-a response which is not NO mediated (Peebles et al 2007)-was unchanged following training, further supporting the suggestion that the training-induced elevation in hypercapnic reactivity is mediated by NO.…”
Section: Effect Of Training On Resting Variablesmentioning
confidence: 99%
“…Although it is well-known that exercise increases BDNF transcription in the brain [8] , recent findings have reported that physical exercise, mostly aerobic endurance exercise, enhances circulating BDNF levels in healthy humans [9][10][11][12][13][14][15][16] . Interestingly, neither high-intensity strength exercise [17] nor general strength training [25] induces any significant changes in BDNF levels.…”
Section: Introductionmentioning
confidence: 99%
“…An elegant review has compared the effects of high-intensity exercise and/ or training on BDNF in healthy subjects with the effects in subjects with chronic diseases [7] . Since the release of BDNF is influenced by aerobic training, which increases the release at rest [16,18] , increased circulating BDNF may depend on the level of physical exertion as well as fitness. In a study by Zoladz and collaborators [18] employing a group of athletes competing in various athletic events (sprinters, jumpers, and distance runners), the basal BDNF levels were compared between trained and untrained sub- Data of BDNF levels were presented as mean ± SEM.…”
Section: Introductionmentioning
confidence: 99%